La señorita Hargreaves - Baker, Frank, 1908-1983 (Rara avis ;, 2013)
When Norman Huntley and his friend Henry invent, on the spur of the moment, an 83-year-old woman called Miss Hargreaves, they are inspired to post a letter to their new fictional friend. It is only meant to be a silly, harmless game - until Miss Hargreaves arrives on their doorstep, complete with her cockatoo, her harp and - last but not least - her bath. She is, to Norman's utter disbelief, exactly as he had imagined her: eccentric and endlessly astounding. He hadn't imagined, however, how much havoc an imaginary octogenarian could wreak in his sleepy Buckinghamshire home town, Cornford. Will his once-ordinary, once-peaceful life ever be the same again? And, what's more, does he want it to be?